2015
DOI: 10.12816/0024929
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus among Viral Causes of Infantile Gastroenteritis

Abstract: Background: Human bocavirus (HBoV) infection possibly plays a role in gastroenteritis because of the frequent manifestation of gastrointestinal symptoms. Objectives: Detect human bocavirus (HBoV) and assess its prevelance among gastroenteritis associated viral agents in infants with gastroenteritis in Benha University Hospital. Methodology: The study was carried out on 100 stool samples collected from 100 infants with acute gastroenteritis for detection of Rotavirus (RV), Norovirus (NoV) & Astrovirus (AstV) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…We suggest the result of this study may be due to the number of male samples collected is higher than the number of female samples, in addition to the superiority of males over females in terms of physical activity in the stages of breastfeeding and childhood. The distribution of human Bocavirus in the current study showing most infection (55.55%) was observed in infant among age group (6-12) months, following by equal percentage (22.22%) for each age group 0-5 months and 13-24months, while no infection noticed in age group (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).This is in agreement with studies carried out in Egypt [18], India [20], South Africa [24] and Brazil [26]. The higher risks at ages 6-12 months and 13-23 months, may be due to diminish of immunity, as the amount of trance-placental antibodies of the child starts dwindling after 6 months of age in addition could be attributed to the fact that children at these age are either crawling or walking and can easily pick dirt or other contaminated objects for playing or eating [27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We suggest the result of this study may be due to the number of male samples collected is higher than the number of female samples, in addition to the superiority of males over females in terms of physical activity in the stages of breastfeeding and childhood. The distribution of human Bocavirus in the current study showing most infection (55.55%) was observed in infant among age group (6-12) months, following by equal percentage (22.22%) for each age group 0-5 months and 13-24months, while no infection noticed in age group (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).This is in agreement with studies carried out in Egypt [18], India [20], South Africa [24] and Brazil [26]. The higher risks at ages 6-12 months and 13-23 months, may be due to diminish of immunity, as the amount of trance-placental antibodies of the child starts dwindling after 6 months of age in addition could be attributed to the fact that children at these age are either crawling or walking and can easily pick dirt or other contaminated objects for playing or eating [27].…”
Section: Discussionsupporting
confidence: 91%
“…The rate of human Bocavirus according to the result of conventional PCR was 9% (9/100 cases). This percentage is close to that of its prevalence in many countries, such as in Iran [13],Taiwan [14], Turkey [15] and Albania [16], where the rates were (8%,8.5%, 8.7%, 9.1% respectively), while this percentage was higher than in other countries such as Russia [17], Egypt [18], South Africa [19], India [20], Bangladesh [21] and Beijing-China [22]. This wide variation among studies could be attributed to the time and period of samples collection, number of samples, the age of the study population, the season, the techniques are used to diagnose the virus, variations in habits, geographical differences, climate changes and the immunological and nutritional situations of individuals, all of these factors may contribute to the difference in the prevalence rates of the virus between studies.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…To our knowledge, limited data are available about the incidence of HBoV in Egyptian children. Only two clinical studies were reported in Egypt; the first study found HBoV in Children with AGE [13]. The second study observed HBoV-1 in children suffering from lower respiratory tract infections without providing any data about different genotypes in the given cases [27].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies detected HBoVs in Europe [7], North America [8], South America [9], the Middle East [10], Asia [11], and Australia [12]. In African countries, HBoVs have been reported in Egypt 2% (2/100 children of age from 1 month to 2 years) [13], Kenya 1.8% (7/384 children/adults) [14], and South Africa 22.8% (174/1460 children < 2 years) [15]. As yet, little is still known about the prevalence of HBoV and its genotypes in Egypt, particularly in children.…”
Section: Introductionmentioning
confidence: 99%